Variation in the chemical profiles of three foxglove species in the central Balkans - Gašić, Uroš; Banjanac, Tijana; Šiler, Branislav; Božunović, Jelena; Milutinović, Milica; Aničić, Neda; Dmitrović, Slavica; Skorić, Marijana; Nestorović Živković, Jasmina; Petrović, Luka; Todorović, Miloš; Živković, Suzana; et al. (Frontiers in Plant Science, 2023)
The aim of this study was to determine intra- and interspecies variation in the qualitative and quantitative composition of methanol-soluble metabolites in the leaves of three Digitalis species (D. lanata, D. ferruginea, and D. grandiflora) from the central Balkans. Despite the steady use of foxglove constituents for human health as valuable medicinal products, populations of the genus Digitalis (Plantaginaceae) have been poorly investigated to describe their genetic and phenetic variation. Following untargeted profiling using UHPLC-LTQ Orbitrap MS, by which we identified a total of 115 compounds, 16 compounds were quantified using the UHPLC(–)HESI–QqQ-MS/MS approach. In total, 55 steroid compounds, 15 phenylethanoid glycosides, 27 flavonoids, and 14 phenolic acid derivatives were identified across the samples with D. lanata and D. ferruginea showing a great similarity, while 15 compounds were characteristic only for D. grandiflora. The phytochemical composition of methanol extracts, considered here as complex phenotypes, are further examined along multiple levels of biological organization (intra- and inter-population) and subsequently subjected to chemometric data analysis. The quantitative composition of the selected set of 16 chemomarkers belonging to the classes of cardenolides (3 compounds) and phenolics (13 compounds) pointed to considerable differences between the taxa studied. D. grandiflora and D. ferruginea were found to be richer in phenolics as compared to cardenolides, which otherwise predominate in D. lanata over other compounds. PCA revealed lanatoside C, deslanoside, hispidulin, and p-coumaric acid to be the main compounds contributing to the differences between D. lanata on one side and D. grandiflora and D. ferruginea on the other, while p-coumaric acid, hispidulin, and digoxin contribute to the diversification between D. grandiflora and D. ferruginea. However, quantitative variation in the metabolite content within species was faint with mild population diversification visible in D. grandiflora and particularly in D. ferruginea. This pointed to the highly conserved content and ratio of targeted compounds within the analyzed species, which was not severely influenced by the geographic origin or environmental conditions. The presented metabolomics approach might have, along with morphometrics and molecular genetics studies, a high information value for further elucidation of the relationships among taxa within the genus Digitalis.